2000
DOI: 10.1007/pl00007283
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of EEG, neuroimaging and histopathology in an epilepsy patient with diffuse cortical dysplasia

Abstract: The correlation between scalp EEG, intraoperative electrocorticogram, neuroimaging and histopathology was examined in a epilepsy child with diffuse cortical dysplasia. A 6-year-old girl with moderate mental retardation had suffered from intractable complex partial and generalized epilepsy since 2-year-old. MR images demonstrated unilateral large macrogyria/polymicrogyria and schizencephaly in the right occipital lobe. The epileptic focus was detected on the macrogyria by EEG and single-photon emission tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…6,7 Invasive electroencephalogram (EEG) recordings have shown that heterotopia, polymicrogyria, and focal cortical dysplasia are all characterized by an intrinsic epileptogenicity, with the generation of isolated or rhythmic epileptiform discharges. [8][9][10] Connectivity with normal brain regions has been confirmed by pathological examination in nodular heterotopia, and visualized by means of diffusion tractography in band heterotopia. 11,12 Moreover, there is evidence that, in some patients with nodular heterotopia, ictal activity may start simultaneously in nodules and cortex.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…6,7 Invasive electroencephalogram (EEG) recordings have shown that heterotopia, polymicrogyria, and focal cortical dysplasia are all characterized by an intrinsic epileptogenicity, with the generation of isolated or rhythmic epileptiform discharges. [8][9][10] Connectivity with normal brain regions has been confirmed by pathological examination in nodular heterotopia, and visualized by means of diffusion tractography in band heterotopia. 11,12 Moreover, there is evidence that, in some patients with nodular heterotopia, ictal activity may start simultaneously in nodules and cortex.…”
Section: Introductionmentioning
confidence: 83%
“…Invasive electroencephalogram (EEG) recordings have shown that heterotopia, polymicrogyria, and focal cortical dysplasia are all characterized by an intrinsic epileptogenicity, with the generation of isolated or rhythmic epileptiform discharges 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…Malformations of cortical development are disorders of cortical formation (proliferation, migration, and differentiation) and are frequently associated with medically refractory epilepsy (Brodtkorb et al, 1998; Hashizume et al, 2000). In selected patients, particularly with focal cortical dysplasia (FCD), resective epilepsy surgery is an option.…”
mentioning
confidence: 99%
“…However, surgery for frontal lobe epilepsy (FLE) has also been reported to be associated with a high failure rate because of difficulties in localizing the epileptic zone and the presence of eloquent areas. In addition, many articles that relate malformations of cortical development (MCD) were already published usually regarding clinical and pathological characteristics, as well as surgical outcomes, but few regarding the practical aspect of the extent of resection3,8,13,19,33).…”
Section: Introductionmentioning
confidence: 99%